FOREWORD - PĂCURAR, Elena; ȘTEFĂNESCU, Maria (Studia Universitatis Babeș-Bolyai Philologia, 2019)
In the 25 years lapsed since the foundation of the Department of Foreign Languages for Specific Purposes at the Faculty of Letters, Babeș-Bolyai University, the educational, socio-political and cultural contexts of learning and teaching modern languages in Romania have shifted at such a pace that it has become rather difficult to predict future changes. Though mainly concerned with (very) local issues regarding the teaching and testing procedures of LSP and LAP students at Babeș-Bolyai University, the Department has always been anchored in both internal and external realities: the international (European) standards of quality language education, national financing, institutional strategies and priorities, the demands of the rapidly-changing labor market, the profile of the new generation of language users etc.